Reconstructing the Criminal Liability of Security Forces for Firearms Misuse from the Perspectives of Positive Law and Islamic Criminal Law - Fathan Wahidan Syamsul Rizal; Maskur Rosyid (al-Rasῑkh: Jurnal Hukum Islam, 2026)
The use of firearms by security forces constitutes an extraordinary exercise of state authority because it is directly related to the protection of citizens' right to life. However, in practice, the use of lethal force often results in casualties outside of real threats, raising the issue of the criminal liability of security forces. This study aims to analyze the criminal liability for firearms misuse by security forces from the perspectives of Indonesian positive law and Islamic criminal law and to compare the two to determine the limits of the legitimacy of the state's use of lethal force. The study employs normative legal methods, drawing on statutory, conceptual, and comparative approaches. Legal materials are analyzed qualitatively through deductive reasoning and systematic interpretation. The results show that positive law assesses liability based on the elements of intent or negligence, and on justifications such as self-defense. In contrast, Islamic criminal law assesses liability based on the classification of multiple errors: ‘amd, shibh al-’amd, and khaṭā’, which are oriented towards protecting life (ḥifẓ al-nafs). A comparison of the two shows that positive law provides legal certainty. In contrast, Islamic criminal law provides an in-depth moral evaluation. The integration of the two approaches results in a model of criminal accountability that treats the use of firearms as a limited authority subject to both legal and ethical controls, thereby strengthening officials' accountability within the criminal justice system. This study contributes theoretically by integrating positive criminal law and Islamic criminal law into a comprehensive model of criminal liability, combining juridical and moral evaluations. Practically, it offers a framework to strengthen law enforcement accountability and prevent impunity in the misuse of firearms.